Hacia una poética del rap feminista: Dimensiones discursivas y estéticas de un género de la literatura contemporánea - Pinilla Alba, Susana (MIMESIS, 2025)
With renowned female rappers such as Ana Tijoux, Rebeca Lane or Gata Cattana, a new way of understanding rap as an anti-patriarchal, political and literary discourse has emerged in the Spanish-speaking world. Drawing on various disciplines, this study seeks to contextualize feminist rap as a theoretical and aesthetic discourse by women and analyze its potential and challenges in today's globalized society.